ECO-Kanban and the systematization of communication in reusing industrial residues:a case study of an automotive glass producer - Zaratin, Miroslava Hamzagic; Francischini, Paulo Graciano (Revista Gestão da Produção Operações e Sistemas, 2012)
Some factors currently influence organization competitiveness in face of global companies: use of cutting-edge technology, knowledge dissemination, concern with environmental issues, and others. This last factor has been of great interest, due to all the changes the world has faced. For all companies, the search for changing processes and eliminating polluting activities has not been easy. One of the biggest difficulties is to insert recycling actions in company activities, taking advantage of practices that have been in use with positive results. Production planning systems and tools like kanban can be one of the examples of these practices, through the systematization of information considered vital for the company. The objective of this study is to present a systematization model for waste information, through the use of kanban, as a means to assist in recycling this waste among members of the production chain. The methodology proposal is experimental, using the test model. The model was tested by four companies, as participants, and the approach is triangular, where qualitative and quantitative aspects will be added to search necessary data for conceiving the model. The results show that when information on the amount and frequency of waste generation is systemized, that is, is shown by the client company in continuous and repetitive forms, as a part of the information system, another company in the chain not only recycles this waste but also adequately provides necessary resources for achieving this recycling flow. It was concluded that systematized information is important for both companies, mainly for planning waste recycling. Therefore, when generation is inevitable, disposal will require all types of resources so it is done adequately.Key-words: Reverse logistics. Systematization. Recycling. Industrial waste. Kanban.